Modeling long recovery early events (LOREs) produced by lightning‐induced ionization of the nighttime upper mesosphere. Issue 7 (25th July 2017) - Kotovsky, D. A.; Moore, R. C.
Abstract: We present results of a cylindrically symmetric, coupled electrodynamic, and photochemical model which simulates diffuse ionization of the middle atmosphere induced by strong lightning discharges (peak currents >150 kA). Scattering of subionospherically propagating, very low frequency radio waves is then evaluated using the Long‐Wave Propagation Capability code. Some modeled sprite halos exhibit continued electron density growth up to timescales of seconds due to O − detachment, though it is not yet clear how this might relate to the slower onset durations (>20 ms) of some early VLF events. Modeled electron density enhancements in sprite halos, capable of strong VLF scattering, can persist for long periods of time (greater than hundreds of seconds) even at lower altitudes where their recovery is initially controlled by fast attachment processes. Consequently, our modeling results indicate that both typical recovery (20 to 240 s) and long recovery (LOREs, >300 s) VLF scattering events can be explained by scattering from conductivity changes associated with sprite halos. In contrast, modeled scattered fields resulting from elve‐associated conductivity changes, though exhibiting long recovery times, are too weak to sufficiently explain typical LORE observations. Theoretical scattering from structured ionization events (e.g., sprites columns and gigantic jets) is not considered in this work. Plain Language Summary: Low‐frequency radio waves propagate efficiently around the globe by reflecting off a region of the middle atmosphere which contains many free and mobile electrons (known as the lower ionosphere). Powerful lightning discharges are capable of directly disturbing the lower ionosphere, resulting in the disruption of those low‐frequency radio waves commonly used for communications. Typically, these disruptions last for only a few minutes. However, some recently observed disruptions can persist for several minutes to tens of minutes. In this work, we model the interaction of lightning with the lower ionosphere and the resulting radio wave disruptions. In particular, this work identifies how long‐lasting radio wave disruptions (persisting for longer than 5 min) are possible. We discuss how the chemistry of the atmosphere effects the duration of radio wave disruptions and identify which aspects of the lightning discharge are most relevant to disturbances of the lower ionosphere. Key Points: Modeled scattering associated with sprite halos can explain both typical recovery and long recovery (LORE) early VLF events Modeled scattering associated with elves is too weak to sufficiently explain typical LORE observations O‐ detachment can result in the continued growth of sprite halo electron densities up to timescales of seconds